Faktor-Faktor Yang Mempengaruhi Kemauan Wajib Pajak Mengikuti Tax Amnesty di KPP Pratama Kota Denpasar - Ni K Lely Aryani Merkusiwati; I Gusti Ayu Eka Damayanthi (Akuntabilitas, 2018)
Tax Amnesty is elimination tax owed should not sanction tax administration and criminal sanctions in field of taxation, by way uncovering treasure and pay ransom money. Based on previous studies, shows the willingness to follow the tax amnesty is influenced by several factors taxpayer awareness, knowledge taxpayer, service tax authorities, and tax penalties. This study aimed to examine the effect of consciousness, knowledge taxpayer, service tax authorities, and tax penalties on the willingness to follow the tax amnesty. Samples in this study as many as 105 people registered taxpayers in east Denpasar and have followed the tax amnesty. The sample in this study was determined by convenience sampling method and slovin formula. Data collected using questionnaires and analysis technique is Multiple Linear Regression. Based on analysis awareness of the taxpayer, the consciousness taxpayer, knowladge taxpayer, the service tax authorities, and tax penalties positive effect on the willingness to follow the tax amnesty.